THE INFLUENCE OF MARKETING STRATEGIES AND CUSTOMER TRUST ON THE LOYALTY OF SAVINGS CUSTOMERS AT PT BPR SWADAYA ANAK NAGARI (SAN) - Mai Yuliza; Erdawati Erdawati; Nadya Septiani (Transpublika Publisher, 2023)
This study aims to determine the effect of Marketing Strategy and Trust on Savings Customer Loyalty at PT BPR Swadaya Anak Nagari (SAN). The population in this study were all savings customers of PT BPR Swadaya Anak Nagari (SAN) with a sample size of 100 people. The sampling technique uses non probability sampling, which does not provide the same opportunity or opportunity to each member of the population when selected as a sample member. This research is associative. The results of this study can be explained where the Marketing Strategy variable has a positive and significant effect on the Loyalty of PT BPR Swadaya Anak Nagari (SAN) savings customers with a regression coefficient of 0.554 with a significant value of 0.000 (<0.05). The Trust variable has a positive and significant effect on the Savings Customer Loyalty of PT BPR Swadaya Anak Nagari (SAN) with a regression coefficient of 0.446 with a significant value of 0.004 (<0.05). While the test results simultaneously have a positive and significant effect on the loyalty of PT BPR Swadaya Anak Nagari (SAN) savings customers with a regression coefficient of 23.568 with a significant value of 0.000 (<0.05). For the test the coefficient of determination gives a contribution of 89.3%. And the remaining 10.7% is influenced by other variables not included in this test.